Isolation and Partial Characterization of Bioactive Fucoxanthin from Himanthalia elongata Brown Seaweed: A TLC-Based Approach - Gaurav Rajauria; Nissreen Abu-Ghannam (International Journal of Analytical Chemistry)
Seaweeds are important sources of carotenoids, and numerous studies have shown the beneficial effects of these pigments on human health. In the present study, Himanthalia elongata brown seaweed was extracted with a mixture of low polarity solvents, and the crude extract was separated using analytical thin-layer chromatography (TLC). The separated compounds were tested for their potential antioxidant capacity and antimicrobial activity against Listeria monocytogenes bacteria using TLC bioautography approach. For bio-autography, the coloured band on TLC chromatogram was visualized after spraying with DPPH and triphenyl-tetrazolium chloride reagents which screen antioxidant and antimicrobial compounds, respectively, and only one active compound was screened on the TLC plate. Preliminary identification of this active compound was done by comparing its colour and Rf (retention factor) value with the authentic fucoxanthin standard. Further, the active compound was purified using preparative TLC. This purified compound showed a strong antioxidant (EC50: 14.8±1.27 µg/mL) and antimicrobial (inhibition zone: 10.27 mm, 25 µg compound/disc) activities, which were examined by DPPH scavenging and agar disc-diffusion bioassay, respectively. The bioactivity shown by the purified compound was almost similar to the fucoxanthin standard. The characteristic UV-visible and FT-IR spectra of the purified active compound completely matched with the standard. Hence, the main active compound in H. elongata was identified as fucoxanthin.